Detection of antioxidant butylated hydroxytoluene (BHT) in Antarctic krill (Euphausia superba Dana). Issue 14 (27th August 2017) - Wang, Mengyao; Liu, Daicheng
ABSTRACT: In this study, butylated hydroxytoluene (BHT) was separated and prepared from Antarctic krill. BHT was separated from the volatile oil of Antarctic krill using high performance thin layer chromatography (HPTLC) with petroleum ether/ethyl acetate/hexane (4:1:0.5, v/v/v) was used as the developing solvent. The content of BHT in volatile oil was 9.20 mg/g and the content of BHT in dried Antarctic krill was 0.35 mg/g (0.070 mg/g in frozen whole Antarctic krill). The linearity, accuracy, stability, and recovery of the analysis showed that HPTLC is the most suitable method for the determination of BHT in Antarctic krill. The BHT crude sample was obtained by scraping the separated spot in the thin layer chromatography plate, which was then analyzed using high performance liquid chromatography (HPLC). The resulting sample was identified with 96.05% purity based on the HPLC analysis. The structure of BHT was determined using gas chromatography–mass spectrometry (GC–MS). The results of the HPLC and GC–MS analysis validated the HPTLC method. BHT is a widely used antioxidant in food, pharmaceuticals, and in industrial production. The exploitation and utilization of BHT in Antarctic krill is of great economic value. GRAPHICAL ABSTRACT: